Prognosis of COVID-19 on Workers with History of Asthma: An Evidence-Based Case Report - Parmitasari, Parmitasari; Fitriani, Dewi Yunia; Widyahening, Indah S (UI Scholars Hub, 2024)
Background. As the COVID-19 pandemic occurs, those with asthma were thought to have an increased risk of infection. Question arisen whether special preparation for severe clinical outcomes might be needed for remote site workers. Method. A literature search was conducted through PubMed, Scopus and ProQuest databases, as well as hand searched. The inclusion criteria were systematic review, cohort study, retrospective study, cross sectional study, COVID-19, asthma, and ICU. Then, they were critically appraised based on Center of Evidence-Based Medicine, Oxford University, Critical Appraisal for Prognostic Studies and Systematic Reviews. Result. Three systematic review studies and three retrospective cohort studies were found. Systematic reviews by Sunjaya, et al. (2021) and Hussein, et al. (2021), also retrospective cohort study by Calmes, MD, et al. (2021) showed no significant difference in risk requiring admission to ICU for asthmatic compared to non-asthmatic (RR 1.19; CI 95%: 0.93 – 1.53; p= 0.16), (RR= 1.64, 95%CI = 0.67-3.97; p=0.27), and (OR = 1.4 (95% CI = 0.64-3.2); p =0.39), respectively. Systematic review by Liu (2021), showed no significant difference in asthma prevalence between ICU and non-ICU patients (RR, 1.19; 95% CI, 0.92-1.54; P =0 .17; I2 = 48.6%;). Cohort study by Choi, et al (2020) showed asthma was not a predictive factor for ICU admission in COVID-19 patients (OR 0.656 (95%CI= 0.295 – 1.440); p value =0.302). Contrary, cohort study by Jin, MMed, et.al (2020) showed that COVID-19 patients with asthma had a higher proportion of ICU admission than those who do not have. Conclusion COVID-19 workers with asthma does not have a higher risk of ICU admission.